Anti-inflammatory Potential of Tithonia diversifolia Leaves in Carrageenan-Induced Edema Model in Mice (Mus Musculus) - Indrisari, Maulita; Khairi, Nur; Muslimin, Lukman; Aksa, Rahmat; Amriani, Amriani; Rahimah, Sitti; Rahayu, Riska (Ad-Dawaa: Journal of Pharmaceutical Sciences, 2025)
Introduction: Edema is a common sign of inflammation characterized by increased tissue volume. Tithonia diversifolia leaves have traditionally been used as anti-inflammatory agents because they contain active compounds such as flavonoids, alkaloids, steroids, terpenoids, tannins, sesquiterpenoids, phenolic acids, and saponins. Aims: Determine the anti-inflammatory effects of ethanol extract of Tithonia diversifolia leaves on rats (Mus musculus) induced by carrageenan. Method: Extraction was carried out using maceration. The experimental design was pre- and post-test with five groups: healthy controls, positive controls (sodium diclofenac), and three treatment groups receiving 12.5 mg/30 gBW, 25 mg/30 gBW, and 37.5 mg/30 gBW of Tithonia diversifolia leaf extract. Edema was induced with carrageenan and measured using a plethysmometer at certain intervals. Result: The results showed that a dose of 37.5 mg/30 gBW significantly decreased edema volume, comparable to the diclofenac group (p>0.05). Conclusion: The ethanol extract of paitan leaves at this dose can function as an effective anti-inflammatory agent.